Results of Surgery Versus Conservative Follow up of Adrenal Incidentaloma (Annals of Medical Research, 2021)
Aim: The incidence of adrenal incidentaloma has increased recently due to increased magnetic resonance imaging (MRI), computed tomography scans (CT) and ultrasonography (USG). In our study, we aimed to demonstrate our radiologic, hormonal and clinical follow up of adrenal incidentaloma
Keywords: Adrenal Incidentaloma; Pheochromocytoma; Adrenocortical Carcinoma.